Determination of the absolute CH4 adsorption using simplified local density theory and comparison with the modified Langmuir adsorption model. Issue 72 (11th December 2018) - Zhang, Yeyu; Zhang, Shaonan; Wang, Zhicheng; Deng, Hucheng; Qi, Minghui; Peng, Xianfeng; Liu, Yueliang
Abstract : Accurately determining the adsorbed amount of CH4 on shale is significant for understanding the mechanisms of shale gas storage and shale methane recovery from shale gas reservoirs. Abstract : Accurately determining the adsorbed amount of CH4 on shale is significant for understanding the mechanisms of shale gas storage and shale methane recovery from shale gas reservoirs. Excess CH4 adsorption is measured using the thermogravimetric method. Simplified local density (SLD) theory is applied to calculate the adsorbed CH4 density to obtain the absolute adsorption. Moreover, the modified Langmuir adsorption model is employed to fit the excess adsorption to describe the absolute adsorption. The adsorbed CH4 density from the SLD model is affected by the system pressure and temperature, while such density obtained from the modified Langmuir model is only a function of temperature. Compared to the modified Langmuir model, the SLD model can better capture the adsorbed CH4 density, which allows accurate determination of the absolute CH4 adsorption.